PENGARUH TERAPI SPIRITUAL GAYATRI MANTRAM TERHADAP KEMAMPUAN KLIEN MENGONTROL HALUSINASI DI RUMAH SAKIT JIWA PROVINSI BALI TAHUN 2018 - Putu Agus Windu Yasa Bukian; Gede Nur Widya Putra (STIKes Buleleng, 2018)
This study aims to analyze the effect of gayatri mantram spiritual therapy toward clients’ capability to control the hallucination in the psychiatric hospital Bali province in 2018. Methods : The design used in this study is pre-experimental research which is one group pre-test and post-test design. The population used in this study are clients who get hallucination in Abimanyu, Sahadewa, Drupadi, and Arimbi rooms. Moreover, the sample of this study are 33 selected volunteers by using purposive sampling technique. The main data of the volunteers are collected by using questionnaire. Furthermore, Wilcoxon test is used by the researcher in this study which results α = 0,05 in terms of significant level.The result of Wilcoxon test showed that the value of p pre and post are (0,023) < α (0,05) which means the Ho of this study is rejected and the Ha is accepted. Based on the result, it can be concluded that there is effects of gayatri mantram spiritual therapy toward clients’ capability to control the hallucination in the psychiatric hospital Bali province in 2018. Therefore, it is expected that the gayatri mantram spiritual therapy to be given routinely by the health personnel to the clients who get hallucination